Analisis Unsur Intrinsik Dalam Film Nussa: The Movie Sutradara Boni Wirasmono Dalam Merepresentasikan Nilai Moral Pada Anak- Anak - Ryan Fadhil Firmansyah; Dani Manesah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
This research is entitled Analysis of Intrinsic Elements in the Film Nussa: The Movie Director Boni Wirasmono in Representing Moral Values to Children. The animated film Nussa: The Movie is an animated film with a family, comedy genre and is popular with children because this type of film is packaged in a funny and interesting way. The animated film Nussa: The Movie was produced by The Little Giantz studio and Visinema Pictures and directed by Bony Wirasmono. The aim of this research is to emphasize the intrinsic elements in the form of characters, plot and setting contained in the animated film Nussa: The Movie directed by Boni Wirasmono. In this research, researchers used qualitative descriptive methods to find the intrinsic elements contained in the animated film Nussa: The Movie.